2016
DOI: 10.3109/21691401.2016.1146727
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive PLGA–curcumin microparticle-embedded chitosan scaffold: in vitro and in vivo evaluation

Abstract: Wound healing is a complex process affected by several factors. In the present work, novel biocompatible PLGA-curcumin microparticle-embedded chitosan scaffold was fabricated for wound-healing application. Process variables involved in the preparation of microparticles were optimized using design of experiment. Scanning electron microscopy (SEM) confirmed the porous nature of scaffold with embedded microparticles. A maximum release of 14% of the encapsulated curcumin was observed at 12th hour. Modified tube di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In the other work, Muthukumar Amirthalingam et al fabricated the novel biocompatible PLGA-curcumin microparticle-embedded chitosan scaffold for wound healing application. Their results indicated that the existent scaffold could be used as a drug delivery system to treat the severe and chronic wounds [94].…”
Section: Poementioning
confidence: 99%
“…In the other work, Muthukumar Amirthalingam et al fabricated the novel biocompatible PLGA-curcumin microparticle-embedded chitosan scaffold for wound healing application. Their results indicated that the existent scaffold could be used as a drug delivery system to treat the severe and chronic wounds [94].…”
Section: Poementioning
confidence: 99%
“…However, MBGs are not optimal for scaffolds because of their high brittleness and low fracture toughness and do not meet the mechanical strength requirements of clinical bone repair, especially in mesoporous form [28,33]. Synthetic bioresorbable polymers are known for their high modifiability because these polymers can be easily fabricated into complex structures [6,15,34,35]. However, their performance in cell attachment, proliferation and osteoconductivity is poor because of the lack of specific cell-recognition signals [36].…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin-loaded, PLGA-embedded chitosan scaffolds were successfully studied for the treatment of chronic wounds. The porous structure of the scaffold supported cell growth and proliferation in Vero cells (in vitro), and the curcumin-loaded composite scaffold displayed more potent antibacterial property against Staphylococcus aureus than the plain scaffold [103]. The novel PLGA-and PLA-based hybrid nanofibers were prepared by electrospinning method, which helped achieve a sustained release of loaded thymosin beta-4.…”
Section: Synthetic Polymer-based Biomaterialsmentioning
confidence: 99%